Microbiological Analysis of Bali Beef with Different Aging Times - Yuliyanti, Karenina Dwi; Adiputra, Kirana Dara Dinanti; Widiarta, I Putu Gede Didik; Nurmasytha, Andi (Universitas Veteran Bangun Nusantara, 2025)
Microbiological analysis of meat is crucial to ensure its safety, quality, and suitability for consumption. As a nutrient-rich medium, beef supports microbial growth, which can impact its quality. This study aimed to characterize the microbiological quality of Bali beef with different aging times. This study used three types of muscles: Longissimus dorsi, Gluteus medius, and Semitendinosus from Bali beef aged ± 3 years and body weight of ± 350 kg. Samples were aged at cold temperatures for 1, 21, and 42 days. A completely randomized design with a 3x3x4 factorial was used in this study. The least Square Means test was applied if the data obtained differed significantly. The research results show that the microbial count in the meat significantly increased during aging for 21 and 42 days. Longer aging periods in this study led to an increase in the microbial count.